The amplification of the mitochondrial genome of the endangered buffy-tufted-ear marmoset Callithrix aurita (Primates: Cebidae) for massive parallel sequencing using the HiSeq 2500 platform. (December 2017) - Amaral, C.R.L.; Silva, D.A.; Amorim, A.; Carvalho, E.F.
Abstract: Callithrix aurita is a native small primate species from the Brazilian Southeastern Atlantic mountains. Considered as vulnerable and figuring the IUCN Red List, the species currently struggles with a reduced population size and faces several obstacles such as congeneric competition and the obvious anthropic pressure. Here we describe our amplification strategy to obtain high quality DNA of the endangered marmoset species Callithrix aurita from the South American Atlantic Rainforest, for use on massive parallel sequencing with the HiSeq 2500 platform. Two fragments of about 9 Kb were successfully amplified comprising the fragments F1 165-9229 and F2 8531-639 of the mitochondrial genome of the Callithrix aurita. The quantification of the DNA was made using the Qubit fluorimeter and the fragments are now under sample preparation and sequencing using the Nextera DNA Kit within the HiSeq 2500 platform.